Answer:
x = -
, x =
![(4)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/njuue06kwccysinu3fvpfi1udnx59yqvei.png)
Explanation:
given 6x² - 5x - 4 = 0
Factorise by considering the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x term, that is
product = 6 × - 4 = - 24 and sum = - 5
The factors are + 3 and - 8
Use these factors to split the middle term
6x² + 3x - 8x - 4 = 0 ( factor the first/second and third/fourth terms )
3x(2x + 1) - 4(2x + 1) = 0 ( take out common factor (2x + 1) )
(2x + 1)(3x - 4) = 0
equate each factor to zero and solve for x
2x + 1 = 0 ⇒ 2x = - 1 ⇒ x = -
![(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ybjkeso7qr5r7js5h0mv9de35dih0sxfpl.png)
3x - 4 = 0 ⇒ 3x = 4 ⇒ x =
![(4)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/njuue06kwccysinu3fvpfi1udnx59yqvei.png)